Work stress and satisfaction in relation to personality profiles in a sample of Dutch anaesthesiologists: A questionnaire survey. Issue 11 (November 2016) - van der Wal, Raymond A.B.; Bucx, Martin J.L.; Hendriks, Jan C.M.; Scheffer, Gert-Jan; Prins, Judith B.
Abstract : Supplemental Digital Content is available in the text Abstract : BACKGROUND: Working in anaesthesia is stressful, but also satisfying. Work-related stress can have a negative impact on mental health, whereas work-related satisfaction protects against these harmful effects. OBJECTIVE(S): How work stress and satisfaction are experienced may be related to personality. Our aim was to study the relationship between personality and perception of work in a sample of Dutch anaesthesiologists. DESIGN: Questionnaire survey. SETTING: Data were collected in the Netherlands from July 2012 until December 2012. PARTICIPANTS: We sent electronic questionnaires to all 1955 practising resident and consultant members of the Dutch Anaesthesia Society. Of those, 655 (33.5%) were returned and could be used for analysis. MAIN OUTCOME MEASURES: The questionnaires assessed general work-related stress and satisfaction and anaesthesia-specific stress. A factor analysis was performed on the stress and satisfaction questionnaires. Personality traits were assessed using the Big Five Inventory. To identify personality profiles, a cluster analysis was performed on the Big Five Inventory. Scores of the extracted factors contributing to job stress and satisfaction were compared between the profiles we identified. RESULTS: Our analysis extracted six factors concerning general job stress. Of those, the emotionally difficult caseload contributed the most to job stress. The analysis also extracted four factors concerning general job satisfaction. Good relationships with patients and their families and being appreciated by colleagues contributed the most to satisfaction. The cluster analysis resulted in two distinct personality profiles: a distressed profile ( n = 215) and a resilient profile ( n = 440). General and anaesthesia-specific job stress was significantly higher and job satisfaction was significantly lower in the distressed profile, compared with the resilient profile. Experience of the emotionally difficult caseload did not differ between the two profiles CONCLUSION: Personality profiles were found to be related to anaesthesiologists' experience of work-related stress and satisfaction. One-third of the anaesthesiologists in our sample were categorised as distressed and are at risk of developing work-related mental health problems.